Extension Mode in Sliding Window Technique to Minimize Border Distortion Effect - Saidatul Habsah Asman; Ahmad Farid Abidin; Nofri Yenita Dahlan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper deals with border distortion effect at starting and ending of finite signal by proposing sliding window technique and basic extension mode implementation. Single phase of transient and voltage sag is chosen to be analyzed in wavelet. The signal which being used for the analysis is simulated in Matlab 2017a. Disturbance signal decomposes into four level and Daubechies 4 (db4) has been chosen for computation. The proposed technique has been compared with conventional method which is finite length power disturbance analysis. Simulation result revealed that the proposed smooth-padding mode can be successfully minimized the border distortion effect compared to the zero-padding and symmetrization approach.